PENGARUH KONVERGENSI IFRS TERHADAP ASIMETRI INFORMASI (STUDY KASUS PADA PERUSAHAAN REAL ESTATE DI INDONESIA) - Rian Aditya Novianto; Nur Cahyonowati (Diponegoro Journal of Accounting, 2014)
This study aims to examine the effect of IFRS aplication on the company to the amount of asymmetric information value which calculate by bid-ask spread stock price. This study uses one independent variable (IFRS), where the effect of this IFRS measured using dummy variable and three control variables, such as DER, ROE, and SIZE to the company. The application of IFRS is predicted can decrease the asymmetric information value.This empirical study uses purposive sampling techniques in data collection where data used is the data of 37 Real Estate and Property companies listed on the JSE during 2011-2012, which is continuously listed on the Stock Exchange and not have negative equity. This study uses linear regression analysis with the help of a computer program called SPSS.The test results showed that the application of IFRS in Real Estate and Property companies significantly influence the increasing amount of the assymetric information value. However, the control variables such as DER, ROE, and SIZE do not show a significant effect on the changing amount of the asymmetric information value.